2009
DOI: 10.1029/2008jd011448
|View full text |Cite
|
Sign up to set email alerts
|

Source origins, modeled profiles, and apportionments of halogenated hydrocarbons in the greater Pearl River Delta region, southern China

Abstract: [1] We analyze 16-month data of 13 major halocarbons measured at a southern China coastal site in the greater Pearl River Delta (PRD). A total of 188 canister air samples were collected from August 2001 to December 2002. Overall inspection indicated that CH 2 Cl 2 , C 2 Cl 4 , and C 2 HCl 3 had similar temporal variations while CFC-11, CFC-12, and CFC-113 showed the same emission patterns during the sampling period. Diurnal variations of halocarbons presented different patterns during ozone episode days, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 70 publications
2
79
2
1
Order By: Relevance
“…Studies have shown that cities in this region suffer from regional air pollution [11][12][13]. As one class of persistent organic pollutants, PAHs can undergo long range atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cities in this region suffer from regional air pollution [11][12][13]. As one class of persistent organic pollutants, PAHs can undergo long range atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we use the NOAA-HYSPLIT4.8 model to calculate backward trajectories at WQS and TC sites during the entire study period, and to carry out particle release simulation for episode days (Draxler and Rolph, 2003). Previous works (Zhang et al, 2009Guo et al, 2009) have demonstrated that the backward particle release simulation, which considers the dispersion processes in the atmosphere, can identify the history of air masses well.…”
Section: Lagrangian Trajectories and Dispersion Simulationmentioning
confidence: 99%
“…We included all CCl 4 enhancement events observed at GSN, thereby representing a better characterization of emission sources throughout East Asia and not just in China. The PMF model has been widely used to identify and apportion sources of atmospheric pollutants (Guo et al, 2009;Lanz et al, 2009;Li et al, 2009;Choi et al, 2010) and is an optimization method that uses a weighted least squares regression to obtain a best fit to the measured concentration enhancements of chemical species (details in the text of the Supplement) and to resolve the number of source factors controlling the observations. A brief mathematical expression of the model is given by Eq.…”
Section: S Park Et Al: Toward Resolving the Budget Discrepancy Of Omentioning
confidence: 99%